Biodegradable hollow mesoporous organosilica-based nanosystems with dual stimuli-responsive drug delivery for efficient tumor inhibition by synergistic chemo- and photothermal therapy. (June 2020) - Chen, Jiajie; Wang, Yitong; Ma, Baoyuan; Guan, Lei; Tian, Zhengfang; Lin, Kaili; Zhu, Yufang
Highlights: Phase-change material (PCM) as responsive "gate-keeper" and CuS nanocrystal were introduced into HMONs. HMONs presented well biodegradability and reducing-enhanced degradation. PCM-gated HMONs@CuS can achieve precise delivery of DOX with dual stimuli-response. HMONs@CuS/DOX@PCM performed effective synergistic chemo-/photothermal therapy. Abstract: Engineering gated porous nanocarriers with multi-stimuli-response is rather fascinating for efficient tumor chemotherapy owing to the avoidance of premature drug leakage and the accurate control of site-specific drug delivery. Herein, a phase-change material (PCM) as a stimuli-responsive ''gate-keeper'' and copper sulfide (CuS) nanocrystal as a photothermal agent were introduced into biodegradable hollow mesoporous organosilica nanoparticles (HMONs) to construct a multifunctional nanosystem for dual stimuli-responsive drug delivery. The capping of PCM on HMONs enabled the prevention of drug leakage and the temperature-responsive drug release manner, and the reducing-responsive biodegradability of disulfide-hybridized HMONs allowed the tumor microenvironment (TME)-sensitive drug release. With the aid of the near-infrared (NIR)-thermal conversion of CuS nanocrystals, the prepared nanosystem could not only realize both endogenous and external stimuli-triggered drug release, but also achieve synergistic effects of chemo- and photothermal therapy for tumor inhibition. In result, such biocompatible and biodegradable PCM-gated HMONs@CuS nanosystem achieved effective delivery of doxorubicin (DOX) and precise drug release at tumor site, and exhibited remarkable in vitro and in vivo tumor inhibition efficacy by combination of chemotherapy and photothermal therapy, showing great prospect in tumor treatment. Graphical abstract: Image, graphical abstract